Instagram Reels Addiction and Academic Procrastination Among Young Pakistani Adults (Journal of Asian Development Studies, 2025)
The use of social media, particularly short-form video content like Instagram Reels, is increasingly popular among young adults. However, there is limited literature exploring the relationship between Instagram Reels usage and academic procrastination, especially among young Pakistani adults. This study aims to address this gap and offer relevant implications. A cross-sectional correlational design and purposive sampling technique were used to collect data from 123 young Pakistani adults (92 men, 31 women) aged 18 to 25 years (M = 24.91, SD = 2.57). The inclusion criteria included being a Pakistani citizen and currently enrolled in college or university, regardless of gender. The Bergen Social Media Addiction Scale and the Academic Procrastination Scale were used to assess the variables. Results showed a significant positive correlation between Instagram Reels addiction and academic procrastination. Moreover, Instagram Reels addiction was a significant predictor of academic procrastination in this population. The study concludes with important implications for managing social media use among young Pakistani adults.